Estimated population size of the people who inject drugs in Thai Nguyen, Vietnam: A two survey capture-recapture study using respondent driven sampling. - Ly Thuy Nguyen; Anindya K De; Kim Anh Ai Le; Cuong Manh Pham; Le Khanh; Van Thi Hai Hoang; Abu S Abdul-Quader (Public Library of Science (PLoS), 2022)
To develop an appropriate programmatic response to the concentrated HIV epidemic, program managers require reliable estimates of the sizes of the key populations. This study attempts to estimate the population size of people who inject drugs (PWID) in Thai Nguyen-a province in the northern part of Vietnam. Two source capture-recapture population size estimates were calculated using data from two respondent driven sampling survey rounds conducted in 5 selected districts from May to August 2019. The population size of the PWID was calculated based on the number of PWID recruited in each survey and 'recaptured' during the first and the second survey. Additionally, personal network size data collected in the RDS was used to measure the population of PWID using the Successive Sampling Population Size Estimate (SS-PSE) method. The population of PWID estimated in five selected districts using the two capture-recapture method (CRC) (median = 5,396, 95% CI: 4,011-9,100) was slightly lower than estimated using SS-PSE with RDS survey 1 (median = 5,580, 95% CI: 3,024-9,272) and higher than when using SS-PSE with RDS survey 2 (median = 4,793; 95% CI: 2,310-8,618). The provincial PWID population estimates based on various approaches (e.g. extrapolation based on the prevalence of PWID in the districts) ranged from 6,498 (95% CI: 4,829-10,957) to around 6,807 (95% CI: 5,341-10,527). A provincial estimate of 6,782 PWID, with a confidence interval ranging from 5,312 to 10,527, will help guide planning and resource allocation to support appropriate levels of HIV prevention, care, and treatment services in the Thai Nguyen province.